Gordon the clever goat: oxford literacy web - Newman, Marjorie; Ambrus, Victor G. (Oxford University Press China, 1999)
An experience of different styles of fiction. They reinforce vocabulary but include a more challenging element to push upward toward the next level. This animal fable is part of the extension stories segment of Stage 4.